Biomedical Application of Carbon Nanotubes for Proteins Extraction and Seperation - Hartmut Schlüter ,; Mohammadreza Saboktakin, (Journal of Pharmacy and Nutrition Sciences, 2016)
Measurement science and technology continue to play vital roles in biomedical research and in routine healthcare. Over recent decades there has been a steady evolution of sensors for biomedical measurement aimed at clinical care in hospitals, fundamental biomedical research in the laboratory, or even self-care in the home. The measurements of interest are diverse, ranging from pressure, force, flow and displacement to electrical field/charge, magnetic flux, and molecular species, such as gases, ions, proteins, bacteria, viruses, and DNA. In this review, we have studied several biomedical applications of nanotubes and nanowires for proteins measurements in cells. Also, These materials have a wide application as protein carriers and transporters. The wide applications of multi-walled carbon nanotubes (MWCNT) on the serious concerns about their safety on human health and environment have been studied.